The Earthscope US transportable array 1 Hz surface pressure dataset. (8th July 2016) - Jacques, Alexander A.; Horel, John D.; Crosman, Erik T.; Vernon, Frank; Tytell, Jonathan
Abstract : A unique set of high temporal frequency surface atmospheric pressure observations have been collected and archived from a large‐scale field campaign in the geosciences. The Earthscope U.S. Transportable Array (USArray TA) consists of approximately 400 deployable surface platforms. Stations were deployed in a Cartesian‐like gridded fashion across a section of the contiguous United States for 1–2 year then retrieved and redeployed as new platforms further east. While primarily deployed for seismic measurements, platforms also recorded surface atmospheric pressure. These pressure data, collected and stored at a temporal frequency of 1 Hz, have been made available via the Research Data Archive at the National Center for Atmospheric Research (NCAR) for the time period 1 Jan 2010–31 Dec 2015. The 6 years of observations contain data from over 1000 locations ranging from the central to eastern United States, as well as some platforms in Alaska and the northwest United States. Data were organized as annual station files with supplemental metadata and quality control summary files. Several web‐based interfaces are also available to rapidly explore the pressure archive. We describe the available dataset with several prominent atmospheric events shown as usage examples.